L’auto-entrepreneuriat : une gestion individuelle du sous-emploi - Sarah Abdelnour (La Nouvelle Revue du Travail)
Self-employment, a business start-up regime that has only been officialised in France since 2009, is depicted in the present article as a tool of income accumulation aimed at increasing the purchasing power of every French citizen - albeit one whose success can mainly be explained, based on statistical sources and about 30 interviews, by high rates of unemployment. With one-third of all self-employed having previously been unemployed, the device can primarily be described as a tool for exiting unemployment, even if its diffusion has largely occurred outside of workforce reintegration schemes. Self-employment can be viewed as a way for unqualified workers or young people trying to start their professional careers to cope with precarious employment. It also helps to circumvent unemployment and the institutional controls and stigma that come with this; serves as private insurance against the risk of underemployment; blurs the lines between the wage system and independent working (and between unemployment and work); and destabilises the very foundations of the wage-earning society.